(untitled) (Semiárida, 2022)
The businesses related to the forestry sector of native forests of La Pampa are little known from an economic-commercial point of view, especially the products that are marketed and the actors that participate. The objective of this work is to describe and analyze the structure and functions of the forest complex of native Pampas forests. With this study, of an exploratory nature, through interviews with qualified participating actors and together with the triangulation of specific secondary information, the aim was to know the realities and potentialities of the activity. For this, the different products obtained from the native forest complex were analyzed, such as firewood, poles and similar, and products derived from logs. Then the social actors involved in the commercial structure of the complex were defined, with their respective characteristics and particular functions; Among these are consumers, distributors, transformer warehouses, sawmills, axe contractors and agricultural producers. The different marketing channels and coordinators for each type of product were described. The importance of forest regulations and informality was identified, highlighting the main critical and leverage points of the complex; relevant information for public and private decision making. Director: Ferro Moreno, Santiago Co-director: Mariano, Roberto Carlos